The Extent of Availability of Reading Comprehension Levels in Assessment Activities in The Fifth Grade Arabic Language Textbook in The Sultanate of Oman - Alajmi, Mohammed Saleh Mohammed; Alsaadi, Sheikha Masuod Salim (Journal of Educational and Psychological Sciences, 2022)
The study aimed at preparing a list of reading comprehension skills that are suitable for fifth-grade students. Moreover, it aimed at revealing the extent of availability of reading comprehension levels in the Arabic language textbook (my beautiful language reading skills) for the fifth grade in the Sultanate of Oman. The researchers used the descriptive approach based on content analysis. The first aim was reached by studying previous studies and preparing a list of reading comprehension skills in six levels: literal comprehension, appreciative comprehension, inferential comprehension, applied comprehension, critical comprehension and creative comprehension students of fifth grade students. While the second objective was achieved by analyzing the sample of the study (372) activities in the first part and the second part. The study introduced several results, including a list of 43 skills distributed at the six reading comprehension levels suitable for fifth-grade students. The book included 38 skills out of a total of 43 reading comprehension skills included in the study instrument. The availability of the six levels of reading comprehension skills rates is varied. The highest is the inferential comprehension 36.74%, followed by a literal comprehension level of 25.98%, followed by a practical comprehension level of 16.01%, followed by a creative comprehension level of 11.54% followed by a critical comprehension level of 5.24%, then a level of comprehension 4.46%.The study had several recommendations, including determining the actual rates of reading comprehension skills that should be available in the studying activities while developing the book and enriching the book with assessment in the skills that the study showed in the six levels.
Keywords: Reading comprehension; Fifth grade; Assessment activities; Arabic language textbook; Coronavirus (Covid- 19) Anxiety & General Education Diploma students at Sultanate of Oman.